THE PROBLEM OF LOYALTY ON THE RHINE RIVER AD 68-70 - Arslantaş, Yüksel; Tosun, Serhat Pir (Hamza ALTIN, 2025)
Legions always held an important place in the administration of the Roman Empire. Winning the loyalty of the legions meant winning the empire. The legions demonstrated their loyalty with an oath called Sacramentum. This oath was considered sacred in Rome, and breaking it meant treason. The events of 68 AD triggered both the Civil War and the Batavian Revolt. The Sacramentum oath was at the heart of the Roman Empire's response to these events. Vindex's uprising against Nero in Gaul played a critical role in this regard. While the Gaul tribes supported Vindex, the Rhine legions in Germania remained loyal to Emperor Nero. After Nero’s death, a problem of loyalty began to arise. Moreover, as seen in the example of Galba, the oaths of allegiance made to the commanders rather than the emperor in the appointments of commanders to the Rhine River led to the rebellion reaching a much larger scale. The most striking reflection of the loyalty problem can be seen in Civilis’ Batavia Rebellion. Indeed, it can be seen that Civilis assessed the loyalty problem and caused a major rebellion.

Roma İmparatorluğu’nun yönetiminde lejyonlar her zaman önemli bir yere sahipti. Lejyonların bağlılıklarını kazanmak imparatorluğu kazanmak anlamına da geliyordu. Lejyonlar, bağlılıklarını Sacramentum adı verilen bir yeminle gösterirdi. Bu yemin Roma’da kutsal kabul ediliyordu ve yeminin bozulması da ihanet anlamına geliyordu. MS 68 yılında yaşanan olaylar hem İç Savaşı hem de Batavia İsyanı’nı tetiklemişti. Roma İmparatorluğu’nun bu hadiselere verdiği reaksiyonların temelinde de Sacramentum yemini bulunmaktaydı. Galya’da Nero’ya karşı Vindex’in ayaklanması bu açıdan kritik bir rol oynamıştı. Galya kabileleri Vindex’e destek verirken Germania’da bulunan Ren lejyonları ise İmparator Nero’ya bağlılıklarını sürdürmüştü. İmparator Nero’nun ölümünün ardından ise sadakat problemi yaşanmaya başlamıştı. Üstelik Galba örneğinde de görüleceği gibi Ren Nehri’ne yapılan komutan atamalarında imparatordan ziyade komutanlara yapılan bağlılık yeminleri isyanın çok daha büyük bir boyuta ulaşmasına neden olmuştu. Sadakat probleminin en güzel yansıması ise Civilis’in Batavia İsyanı’nda görülebilmektedir. Nitekim Civilis’in sadakat problemini değerlendirip büyük bir isyana sebep olduğu görülebilir.
REN NEHRİNDE SADAKAT PROBLEMİ MS 68-70
Keywords: Classical Greek and Roman History; Eski Yunan ve Roma Tarihi